EXTENSION PARTICIPATION AND ITS PREDICTORS: A STUDY OF MAIZE FARMERS IN THE FFBS PROGRAM ACROSS KADUNA AND KANO STATES - Effiong, M. I.; Abbas, S.; Mohammed, G.; Makwin, F. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the factors that shape maize farmers' participation in the Farmer Field Business School (FFBS) program in Kaduna and Kano States, Nigeria. A multistage random sampling technique was used to select 496 respondents. Data were collected through the use of structured questionnaires and analayzed using dDescriptive and inferential statistics. Findings showed that most respondents were male (83.1%), married (86.5%), literate (87.9%), with a mean age of 42 years, and an average farming experience of 20 years. The results of the logit model revealed that years in farming (4.29), mode of land acquisition (1.99), years in cooperative society (3.52), and FFBS awareness (z = 7.87***) were significant positive drivers of participation. Conversely, older age (−3.00) and higher education (−2.22) were negative and significant (P<0.01) and (P<0.05) in influencing participation in shaping farmers participation in FFBS programme in the study area. The study recommends that stakeholders strengthen extension services and cooperative networks as strategic entry points for boosting FFBS participation and improving farmer productivity.